Anti-GQ1b Antibody Syndrome with Visual Impairment: A Retrospective Case Series - Zeng, Qing; Li, Juan; Feng, Shu-Xing; Xiao, Pei-Yao; Zheng, Yi-Fan; Zhang, Cheng; Liao, Song-Jie (Journal of integrative neuroscience, 2022)
Background: Anti-GQ1b antibody syndrome referred to a clinical spectrum characterized by acute onset of ataxia, ophthalmoplegia and areflexia, while visual deterioration was rarely reported in terms of ocular disorders. This study aimed to describe the clinical characteristics of anti-GQ1b antibody syndrome with visual impairment. Methods: The database at the First Affiliated Hospital of Sun Yat-sen University was searched from 2014 to 2020. Patients with anti-GQ1b IgG were identified and divided into two groups according to the existence of optic neuropathy. Clinical and laboratory data of these subjects between the two groups were collected and analyzed. All patients were followed up by telephone to assess the outcome. Results: A total of 12 patients with seropositive anti-GQ1b antibody were included, 75% of which got antecedent infection. Of these cases, 3 showed visual deterioration accompanied by abnormal orbital magnetic resonance imaging or visual evoked potentials, and the other 9 didn’t show any evidence of vision impairment. Patients in the optic neuropathy group presented prominent visual impairments as initial symptoms and were more likely to suffer from facial weakness. There were 4 patients in normal visual acuity group complaining of blurred vision due to intraocular muscle paralysis, which was distinguished by subsequent examination. The combination of glucocorticoids and intravenous immunoglobulin was applied to treat patients with optic neuropathy. Conclusions: This study provides strong evidence that anti-GQ1b antibody syndrome can exhibit visual impairment, which helps further expand the clinical spectrum of anti-GQ1b antibody syndrome. More attention should be paid to the physical and supplementary ophthalmological examination to explore the pathogenesis and treatment of anti-GQ1b antibody syndrome.